A new paleomagnetic constraint on the duration of a twin caldera-forming eruption sequence: a potential solution to an enduring problem in decoding >VEI 7 eruption timescales - Darren M. Gravley; Takeshi Hasegawa; Nobutatsu Mochizuki; Chie Kusu; Makoto Okada (Earth, Planets and Space)
Abstract New paleomagnetic results from the twin caldera-forming Mamaku–Ohakuri eruption deposits in the Taupō Volcanic Zone of New Zealand show that the entire pyroclastic sequence accumulated within a geomagnetic excursion event. The deposits are predominately unconsolidated and include multiple airfall ash units and two caldera-forming ignimbrites. The older Mamaku ignimbrite is moderately welded and has been previously correlated with the ~240 ka Mamaku excursion. By utilizing a refined technique to extract samples from multiple units in the eruption sequence (including the Mamaku ignimbrite) and measuring mean characteristic remanent magnetization directions, we establish that the entire sequence may have occurred over decades to centuries, and that the geomagnetic directional changing rate probably fluctuated significantly during the excursion, up to several degrees per day. More research is required, but we argue that sequences of relatively rapidly deposited pyroclastic material have significant potential in not only refining the timescales of volcano explosivity index (VEI) 7 and larger VEI 8 eruptions, but also as an alternative recorder that could progress some well-documented and unanswered questions in paleomagnetic research, like the stop-and-go character of the geomagnetic field direction during excursions and reversals. Graphical Abstract